Factors influencing worker preference toward employment in private sector a case study at Pengkalan Chepa Industrial Area / Omar Farruqi Che Harun - Che Harun, Omar Farruqi (2014)
This study is aimed to identify the best factor that influencing worker preference toward employment in private sector. The study was conducted among worker at Pengkalan Chepa Industrial Area, Kelantan. The main objectives of this study are to identify the factors influencing worker preference toward employment in private sector and to determine the relationship between the worker preference with the wages of the job, employee benefits, and level of education. The sample of the study was workers in companies at Pengkalan Chepa Industrial Area, Kelantan. The questionnaires consisted five sections which are question of worker preference, question of wages, question of employee benefit and question of level of education. The researcher distributed 100 sets of questionnaires to the respondents and only 80 sets that the researcher gets back. From the analysis by using SPSS, the researcher can conclude that the objectives of the research which are to identify the factors influencing worker preference toward employment in private sector and to determine the relationship between the worker preferences with the wages, employee benefits and level of education were accomplished. From the data finding also, the researcher was answered the research question which are what are the factors influencing worker preference toward employment in private sector and Is there any relationship between worker preference with the wages, employee benefit and level of education. Lastly, the factor influencing worker preference toward employment in private are wages, employee benefits, and level of education at Pengkalan Chepa Industrial Area